Uncovering the hidden mechanics of upper body rotations in tennis serves using wearable sensors on Dutch professional players - B. van Trigt; B. van Trigt; E. Faneker; E. Faneker; A. J. R. Leenen; A. E. Hoekstra; M. J. M. Hoozemans (Frontiers in Sports and Active Living)
BackgroundIt is assumed that the tennis serve is performed according to the kinetic chain principle in which a proximal-to-distal sequence in peak angular velocities of subsequent body segments can be observed to reach high end point ball velocities. The aim of the present study was to investigate if the magnitude and (intersegmental) timing of peak angular velocities of body segments in professional tennis players are different between first and second serves and if they are associated with serve performance.MethodsEight (two female and six male) professional tennis players performed each 48 tennis serves on a tennis court. Serve performances: Ball speed and accuracy were measured with a PlaySight system. Kinematics were assessed with a custom made high-end inertial measurement units (IMUs) system, sampled at 1,000 Hz. Magnitudes of, as well as the intersegmental timing between, three dimensional peak angular velocities of the pelvis, trunk, and dominant upper arm were analysed in relation to ball speed and accuracy with generalized estimating equations.ResultsPeak angular velocities of the pelvis, trunk and upper arm were significantly higher in the first compared to the second serve. The intersegmental timing did not show significant differences. Also, the intersegmental timing was not associated with the ball speed. Ball speed was significantly positively associated with peak angular velocities of the trunk and upper arm on both the first and second serve. Accuracy was positively associated with the peak trunk angular velocity and intersegmental timing between the pelvis and trunk in the first serve. Accuracy was negatively associated with peak trunk angular velocity in the second serve.ConclusionThe arm movement is important to produce high ball speed during a tennis serve. Additionally, the trunk, proximal to the upper arm in the kinetic chain, showed associations with ball speed. In contrast to the upper arm also with accuracy. Interestingly, professional players do not strictly follow a proximal-to-distal sequence. Intersegmental timing appears to be less important in the tennis serve compared to the segmental angular velocities, which were higher in the first compared to the second serve. Future research should investigate the uncovered role of the trunk in relation to tennis serve performance.